LABOR AND GENDER EXPLOITATION IN CHIMAMANDA NGOZI ADICHIE’S AMERICANAH NOVEL: MARXIST FEMINIST ANALYSIS - Anggy Rahayu Larasati; E. Ngestirosa Endang Woro Kasih (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
This research aims to analyze the Marxist feminist of the novel